Academy of the oppressed : Paulo Freire and how academics lost control of the university - Heffernan, Troy (Emerald Publishing Limited, 2024)
There is a need for constant assessment of an ever-changing leadership landscape, especially in universities, as we move towards the mid-twenty-first century. Decades of university reform has turned higher education into a system of corporate universities led by millionaire executive teams who are accountable to each other, university boards and senates, and governments, but rarely students or academics - with academics being the most disposable component of the equation. Academy of the Oppressed approaches potential university reform as a system that has gone far beyond institutions being for scholars, led by scholars, driven by the creation and dissemination of knowledge, and separated from the influence of government and business. Heffernan takes Friere's primary works as a theoretical guide to dissect how university leaders and leadership teams (the oppressors) have slowly eroded the power the academic body (the oppressed) once had in guiding the institution and themselves. The important insights collated here provide guidance to progress towards institutions where academics possess more control of the policies that guide their careers, the knowledge they create, the knowledge they share, the students they inspire, and the communities they aim to serve.
Includes index.
Keywords: Educational leadership.; Education, Higher -- Aims and objectives.; Universities and colleges -- Political aspects.; Education / Schools / Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books